Citizenship studies - Johnson, Steve; Roffe, Graeme (Dynamic learning, 2016)
An OCR endorsed textbook.Association for Citizenship Teaching Quality Mark resource. Encourage students of all abilities to develop an enthusiastic interest in contemporary UK society with knowledge-boosting activities and assessment support for the changed content and assessment criteria; produced by the leading Citizenship publisher and OCR's Publishing Partner.- Equip students with the knowledge and skills they need to fulfil their potential by working through a variety of developmental activities that are suitable for all ability levels- Provide opportunities for students to learn and practise the research, analytical, interpretative and evaluative skills required under the 2016 specification- Bring the key issues and concepts in Citizenship Studies to life using a bank of real-life case studies to enrich students' learning experience- Build students' confidence approaching assessment with targeted assessment preparation, guidance on crafting successful responses and practice questions that include plenty of source analysis tasks- Deliver high-quality lessons that meet the differing needs of your students, following an engaging teaching pathway created by a skilled teacher with extensive examining experience